Politically Motivated Prosecutions and Detentions: Grand Chamber judgment in the case of Selahattin Demirtaş v. Turkey (no. 2) - Cinar, Ozgur H. (Border Crossing, 2021)
This is a commentary paper by focusing on the European Court of Human Rights’ judgment in the case of Selahattin Demirtaş v. Turkey (no. 2). It is a controversial judgement which has received substantial international attention. In this case, the Court has been given the opportunity to reiterate its key positions on a highly important aspect of freedom of expression (Article 10), the right to liberty and security (Article 5) and the right to free elections (Article 3 of Protocol No. 1).